Real‐world data reveal unmet clinical needs in insulin treatment in Asian people with type 2 diabetes: the Joint Asia Diabetes Evaluation (JADE) Register. Issue 4 (3rd February 2020) - Kong, Alice P. S.; Lew, Thomas; Lau, Eric S. H.; Lim, Lee‐Ling; Kesavadev, Jothydev; Jia, Weiping; Sheu, Wayne H.‐H.; Sobrepena, Leorino; Tan, Alexander T. B.; Nguyen, Thy Khue; Yoon, Kun‐Ho; Wang, Ke; et al.
Abstract: Aims: To explore the pattern of insulin use and glycaemic control in Asian people with type 2 diabetes, stratified by gender, young‐onset diabetes (YOD; diagnosed before age 40 years), and diabetic kidney disease (DKD; estimated glomerular filtration rate [eGFR] < 60 mL/min/1.73m 2 ). Materials and methods: We conducted a cross‐sectional analysis of 97 852 patients from 11 Asian countries/regions (2007–2017) included in the prospective Joint Asia Diabetes Evaluation (JADE) Register. Results: Among 18 998 insulin users (47% women, mean ± SD age 59.2 ± 11.7 years, diabetes duration 13.2 ± 8.3 years, glycated haemoglobin [HbA1c] 72 ± 21.4 mmol/mol [8.74 ± 1.95%], median total daily insulin dose [TDD] 0.27–0.82 units/kg), 25% and 29.5% had YOD and DKD, respectively. Premixed (44%) and basal‐only (42%) insulin were the most common regimens. Despite being more commonly treated with these two regimens with higher insulin dosages, patients with YOD had worse HbA1c levels than their late‐onset peers (73 ± 20.5 vs. 71 ± 21.2 mmol/mol [8.82 ± 1.87% vs. 8.66 ± 1.94%]; P  < 0.001). Fewer women than men attained an HbA1c level < 53 mmol/mol (7%; 15.7% vs 17.1%; P = 0.018). Adjusting for age, diabetes duration, TDD, HbA1c, eGFR, and use of oral glucose‐lowering drugs at baseline, the odds of self‐reported hypoglycaemia were higher in women (vs. men: adjusted odds ratio [aOR] 1.16, 95% confidence interval [CI] 1.05–1.28) and in patients with DKD treated with a premixed regimen (1.81 [95% CI 1.54–2.13] vs. 1.34 [95% CI 1.16–1.54] in non‐DKD; P interaction  < 0.001). Compared to basal‐only regimens, premixed and basal‐bolus regimens had similar HbA1c reductions but were independently associated with increased odds of hypoglycaemia (1.65 [95% CI 1.45–1.88] and 1.88 [95% CI 1.58–2.23], respectively). Conclusions: In this Asian population, there were varying patterns of insulin regimens with suboptimal glycaemic control, despite relatively high TDDs, which were influenced by gender, DKD, and YOD status.